Vluchtlijnen van de poëzie Over het werk van Jeroen Mettes - Bluijs, Siebe; ieven, bram (SEL, 2022)
In Vluchtlijnen van de poëzie, Mettes' experimental poetry and political essayism are the starting point for a creative reading and (re)interpretation of recent poetry history. The book takes the reader from Mettes to Friedrich Hölderlin, Herman Gorter, Gertrude Stein, Sybren Polet, J.F. Vogelaar, Ron Silliman, Dominique De Groen, Hannah van Binsbergen and many others. The poetic galaxy that is created in this way offers insight into the relationship between politics, poetry and form.